Photobiomodulation as adjuvant therapy for Bell's Palsy: a case series - Leme Silva, Fernanda (2024)
This study evaluated the efficacy of low-level light therapy (LLLT) in the treatment of three patients with Bell's palsy (BP) and reviewed relevant literature. The first case involved a 52-year-old woman with grade V BP, who, after receiving pharmacological treatment and undergoing seven sessions of LLLT (780 nm; 70 mW; E = 9 J), improved to grade II within 21 days. The second case was a 37-year-old man who, having previously shown no response to treatment, received 24 sessions of LLLT and progressed from grade V to grade II over the course of 4 months. The third case involved a 40-year-old man who, following medication and eight sessions of LLLT, improved from grade V to grade I in 1.5 months. Overall, LLLT was found to significantly enhance facial function, aesthetics, and overall well-being in these patients within a relatively short period.